Soberania petrolífera e(m) estado de exceção - Lima, Yago Roberto Lopes Correia (2024)
More than thirty years have passed since the promulgation of the 1988 Constitution, but it continues to be a national obstacle to develop according to the principles listed in that Major Law. National oil is regulated by several provisions of the constitutional text, as the original constituent considered the aforementioned mineral good strategic for the implementation of objective norms (normas di scopo). Despite this, Brazil is at the forefront of backwardness and Petrobras' economic scenario is dismantling. The work in question aims to expose the three phases that explain the current critical moment of the aforementioned state-owned company: monopolistic, flexible and destruction.